الخلوة وتأثيرها في استقرار المهر دراسة مقارنة - محمد, شمال عبدول; محمود, محمود عبد الله (Sulaimani Journal for Humanities, 2022)
This study attempts to clarify the scholars’ doctrines about the effect of seclusion on the stability of the dowry, by explaining the correct seclusion, the impediments to seclusion and its types, and mentioning the evidence of each group and the way they inferred them, with their discussion and statement of the preferred and the weak ones. The research also touched on the effects of seclusion in terms of changing norms and the ease of being alone with each other by dividing the research into four sections, and in the conclusion, we indicated the points that emerged from the study with some recommendations related to the subject of the study.